2020
DOI: 10.1021/jasms.0c00331
|View full text |Cite
|
Sign up to set email alerts
|

HRMS Detector for the New HILIC CBD Method Development in Hemp Seed Oil

Abstract: The cannabis analysis has gained new importance worldwide due to the rapid expansion of the hemp global market. Many reverse phase high performance liquid chromatography (HPLC) methods have been developed to analyze cannabidiol (CBD) and its analogues due to the nice fit with their log P values at around 6. However, when CBD was blended with hemp seed oil in consumer, cosmetic, and food industries, the high content of triacylglycerides (TAGs) from hemp seed oil were retained and accumulated inside C18 columns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…The challenge to simultaneously quantify CBD and hemp seed oil TAG was reported in our previous study [11]. We found that the common mobile phases like methanol and acetonitrile cannot effectively elute TAGs out from reverse phase columns.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The challenge to simultaneously quantify CBD and hemp seed oil TAG was reported in our previous study [11]. We found that the common mobile phases like methanol and acetonitrile cannot effectively elute TAGs out from reverse phase columns.…”
Section: Introductionmentioning
confidence: 76%
“…The next challenge was how to characterize the separated TAG peak as a chemical marker for CBD hemp seed oil quantification. The TAG structures can be profiled and characterized by using chromatographic techniques [11,21]. Fragmentation patterns and neutral loss in mass spectrometry have been used for the quantification of regioisomers with minimal standards [22,23], and the online acetone Paterno-Buchi reaction and ultraviolet photo-dissociation coupled with mass spectrometry was recently used to determine the double bond position in TAG structures [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The RSDs of the CBD calibrators used to develop the calibration curves were less than 10%, and no analyte signal was observed in the unspiked chocolate and gummy matrices (example shown in Figure S6). Several studies (presented in Table ) have reported the successful quantification of cannabinoids in Cannabis -infused matrices such as oils/liquids, ,,,,, food products, ,,,,,, concentrates, capsules, ,, and vape products. , Ciolino et al reported the average percent (%) recovery of five cannabinoids in various spiked matrices, including edible oils, foods, topicals, oral OTC (over-the-counter) pharmaceuticals, beverages, and dairy foods . Included within the food product category were milk and dark chocolate bars (extracted with acetonitrile) and a hard candy (extracted with 83% aqueous acetonitrile) …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the core silica material used in normal phase HPLC provides alternative retaining power by adsorptive interaction, which was thoroughly described by Prof. Irgum in his HILIC methodology review [42]. This adsorptive interaction between core silica and analytes can be easily observed in cannabidiol (CBD) separation from hemp seed oil by the HILIC method when the ACN concentration reaches 99% [43]. This interaction provides additional separation opportunities for complicated analytes, especially when several types of functional groups were present [44].…”
Section: Resultsmentioning
confidence: 99%